Genome-wide analysis identifies gain and loss/change of function within the small multigenic insecticidal Albumin 1 family of Medicago truncatula. Issue 1 (December 2016) - Karaki, L.; Da Silva, P.; Rizk, F.; Chouabe, C.; Chantret, N.; Eyraud, V.; Gressent, F.; Sivignon, C.; Rahioui, I.; Kahn, D.; Brochier-Armanet, C.; Rahbé, Y.; et al.
Abstract Background Albumin 1b peptides (A1b) are small disulfide-knotted insecticidal peptides produced by Fabaceae (also called Leguminosae). To date, their diversity among this plant family has been essentially investigated through biochemical and PCR-based approaches. The availability of high-quality genomic resources for several fabaceae species, among which the model speciesMedicago truncatula (Mtr ), allowed for a genomic analysis of this protein family aimed ati) deciphering the evolutionary history of A1b proteins and their links with A1b-nodulins that are short non-insecticidal disulfide-bonded peptides involved in root nodule signaling andii) exploring the functional diversity of A1b for novel bioactive molecules. Results Investigating theMtr genome revealed a remarkable expansion, mainly through tandem duplications, of albumin1 (A1) genes, retaining nearly all of the same canonical structure at both gene and protein levels. Phylogenetic analysis revealed that the ancestral molecule was most probably insecticidal giving rise to, among others, A1b-nodulins. Expression meta-analysis revealed that many A1b coding genes are silent and a wide tissue distribution of the A1 transcripts/peptides within plant organs. Evolutionary rate analyses highlighted branches and sites with positive selection signatures, including two sites shown to be critical for insecticidal activity. Seven peptides were chemically synthesized and folded in vitro, then assayed for their biological activity. Among these, AG41 (aka MtrA1013 isoform, encoded by the orphan TA24778 contig.), showed an unexpectedly high insecticidal activity. The study highlights the unique burst of diversity of A1 peptides within theMedicago genus compared to the other taxa for which full-genomes are available: no A1 member inLotus, or in red clover to date, while only a few are present in chick pea, soybean or pigeon pea genomes. Conclusion The expansion of the A1 family in theMedicago genus is reminiscent of the situation described for another disulfide-rich peptide family, the "Nodule-specific Cysteine-Rich" (NCR), discovered within the same species. The oldest insecticidal A1b toxin was described from the Sophorae, dating the birth of this seed-defense function to more than 58 million years, and making this model of plant/insect toxin/receptor (A1b/insect v-ATPase) one of the oldest known.